2016
DOI: 10.1007/s11033-016-4017-8
|View full text |Cite
|
Sign up to set email alerts
|

The c.−190 C>A transversion in promoter region of protamine1 gene as a genetic risk factor for idiopathic oligozoospermia

Abstract: The genome condensation in the sperm head is resulted with replacing of histones by protamines during spermatogenesis. It is reported that defects in the protamine 1 (PRM1) and/or 2 (PRM2) genes cause male infertility. Located on chromosome 16 (16p13.2) these genes contain numerous unstudied single nucleotide polymorphisms. This study aimed to investigate the association of c.-190 C>A and g.298 G>C transversions that respectively occur in PRM1 and PRM2 genes with idiopathic oligozoospermia. In a case-control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Jamali, Karimian, Nikzad, and Aftabi () assessed the PRM1 c.‐190 C>A polymorphism and its association with semen parameters. Their results showed similarity to the present study as there was a significant association between ‐190CA and ‐190AA genotypes with oligozoospermia (Jamali et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jamali, Karimian, Nikzad, and Aftabi () assessed the PRM1 c.‐190 C>A polymorphism and its association with semen parameters. Their results showed similarity to the present study as there was a significant association between ‐190CA and ‐190AA genotypes with oligozoospermia (Jamali et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Jamali, Karimian, Nikzad, and Aftabi () assessed the PRM1 c.‐190 C>A polymorphism and its association with semen parameters. Their results showed similarity to the present study as there was a significant association between ‐190CA and ‐190AA genotypes with oligozoospermia (Jamali et al, ). In addition, the study found no association between the g.298 G>C transversions that occur in PRM2 genes with oligozoospermia (Jamali et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For rs1646022, nine studies were selected from 2003 to 2016, which met our inclusion criteria, including 1558 cases and 1137 controls (Aoki, Christensen, Atkins, & Carrell, ; Grassetti et al., ; Jamali et al., ; Jodar et al., ; Li et al., ; Tanaka et al., ; Tüttelmann et al., ; Venkatesh et al., ; Yang et al., ). No significant correlation of this SNP, located in the intronic area of the PRM2 gene in chromosome 16p13.2, was observed with male sterility in our overall analysis using a variety of different models.…”
Section: Discussionmentioning
confidence: 99%
“…Infertility is the inability to become pregnant after 1 year of unprotected intercourse and affects approximately 10%–15% of couples; 20% of these cases involve male factors while 40% involve both male and female factors (Agarwal, Mulgund, Hamada, & Chyatte, ; Jiang, Sun, et al., ; Jiang, Zhang, Xia, & Xu, ; Pan et al., ; Yang, Liu, Li, Song, & Tan, ). Spermiogenesis is the process in which male germ cells differentiate from haploid round spermatids to motile spermatozoa with flagella (Jamali, Karimian, Nikzad, & Aftabi, ; Liu et al., ). This is a process in which first transition proteins sequentially replace the majority of the core histones to allow protamines (PRM) to facilitate the hyper compaction of chromatin (Neto, Bach, Najari, Li, & Goldstein, ).…”
Section: Introductionmentioning
confidence: 99%
“…The mentioned changes are evaluated by bioinformatics tools. Some previous reports revealed that bioinformatics was an effective device to assess molecular biology and specially to examine the molecular effects of gene polymorphisms (Jamali et al, 2016;Soleimani et al, 2017;Zamni-Badi et al, 2018b;Teimouri et al, 2018;Mobasseri et al, 2019). Therefore, in silico tools were employed in this study to evaluate the effects of C524T polymorphisms on the MTRR molecular aspects.…”
Section: Genetic Association Analysismentioning
confidence: 99%